URGENSI DIGITAL PARENTING UNTUK MENCEGAH KECANDUAN GADGET PADA ANAK USIA DINI DI DESA KARANGKLESEM PURBALINGGA - Riris Eka Setiani (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
The use of gadgets among early childhood has experienced a significant increase, especially after the Covid-19 pandemic, which encouraged the intensification of digital-based learning. This condition has the potential to lead to gadget addiction if not accompanied by appropriate parenting patterns. This community service activity aims to improve parents' understanding and skills in implementing Islamic digital parenting as an effort to prevent gadget addiction in early childhood in Bagelan Village, Purworejo Regency. The method of implementing this community service activity was carried out through several stages, namely socialization, counseling, interactive discussions (limited FGD), and assistance to parents. The approach used is community-based training that focuses on increasing parents' capacity in using gadgets appropriately according to the child's developmental stage, as well as strengthening Islamic parenting values in the digital environment. The results of the activities show an increase in parents' understanding of the positive and negative impacts of gadget use, the importance of limiting usage duration, selecting educational content, and implementing supervision and role modeling based on Islamic values in children's digital media use. In addition, participants showed a positive response to the materials and guidance provided. Thus, the Islamic digital parenting program can be an effective educational strategy in supporting healthy digital parenting patterns and preventing gadget addiction in early childhood.